The Effect Of Mechanical Vibration On The Cell Hydration In Rat Brain Cortex And Cardiac Tissues And Pain Threshold - Musheghyan, G. Kh.; Madoyan, G. K.; Azizyan, A. E.; Sargsyan, G. V.; Arajyan, G. M. (Մանկավարժ հրատ․)
The effect of horizontal mechanical vibration 4Hz, 30dB of 10 minutes duration on pain threshold and hydration rate of brain cortex and cardiac tissues samples has been examined on rats. The experiments were performed in vivo and in vitro on the intact and experimental groups of the animals to check the changes in cell metabolic regulation. Additional the changes in the rats’ fecal pH gradient have been assessed. For in vitro experiments the studied tissue samples were incubated to 30 minutes in Tiroide physiological solution. Also for estimation of the number of the membrane receptors [Na+/K+ ATPases] the studied tissues were incubated in the Na+/K+ exchange pump specific inhibitor [3+H]-ouabain of 10-9 and 10-4 M solutions for 30 minutes. Obtained results revealed that treatment with mechanical vibration (4Hz, 30dB, 10min) resulted in a 105% increase in pain threshold value, which is the reduction in pain sensitivity, directly correlating with the rate of hydration changes, in particular of 14.6% dehydration. The experimental data revealed certain orderliness between the changes in cell hydration level and pain threshold in brain studied tissues and cardiac tissue, which is set in between the functional activity of the hydration of the nervous and muscular systems. This can be considered as the basis for the hypothesis according to which the cell volume can be used as a cell marker to characterize the functional state of the different tissue cells. In vivo և in vitro պայմաններում բջջի նյութափոխանակության գործընթացում նկատվող փոփոխությունը գնահատելու նպատակով հետազոտվել է 4Հց հաճախականությամբ, 30դԲ ուժգնությամբ, հորիզոնական դիրքով, մեխանիկակական վիբրացիայի ազդեցությունն առնետների ցավի շեմի արժեքի և գլխուղեղի կեղևի, սրտի հյուսվածքների նմուշների հիդրատացիայի ցուցանիշի վրա: In vitro պայմաններում իրականացվող փորձերում, վերը նշված հյուսվածքների նմուշները ենթարկվել են 30րոպե տևողությամբ ինկուբացիայի Թիրոդեի ֆիզիոլոգիական լուծույթում: Բացի այդ, հյուսվածքների նմուշներում թաղանթի ընկալիչների [Na+/К+ ԱԵՖ-ազների] թվի գնահատման նպատակով, նմուշները 30րոպե տևողությամբ ենթարկվել են Na+/К+ փոխանակիչի գործունեությունը ընկճող [3+ H]–օուաբաինի 10-9Մ и 10-4Մ կոնցենտրացիաներով լուծույթներում: Ստացված արդյունքերը վկայում են, որ 4Հց հաճախականությամբ, 30դԲ ուժգնությամբ, մեխանիկակական վիբրացիան 105%-ով հանգեցնում է կենդանիների ցավի շեմի արժեքի բարձրացմանը, այսինքն ցավազգայնության ցուցանիշի իջեցմանը, որը 14,6%-ով կորելացվում է հյուսվածքների ջրազրկմամբ (14,6%-ով): Для того чтобы оценить изменения в клетках, замечаемые в процессе обмена веществ при условии in vivo и in vitro было изучено влияние механической вибрации при чаcтоте 4Гц, силе 30дБ, в горизонтальном состоянии, на значение шкалы боли и гидратации коры головного мозга и сердечного слоя у крыс. Во время опытов в условии in vitro, приведенные выше примеры слоев были обработаны физиологическим раствором Тироидеи в течение 30 минут. Кроме того, для того, чтобы оценить количество приемников Na+/К+ АТФ в оболочке в слоях, они были обработаны 10-9М և 10-4М растворами [3+H] оуабаина, который улучшает деятельность заменителя Na+/К+ в течение 30 минут.
Keywords: Neurobiology; Vibrations